How to do things with legal doctrine - Schlag, Pierre (The University of Chicago Press, 2020)
"The concept of legal doctrine and its role in how we understand the structure of law has changed over time, especially with the critique of formal law by American legal realists and their insistence on the pliability of law. And yet doctrine remains central to the expression and analysis of law in the judiciary and among practicing lawyers. Recently interest in doctrine as a legal form that embodies and expresses legal arguments, principles, policies, and values, has revived. Pierre Schlag and Amy J. Griffin seek to further the study of doctrine. How to Do Things with Legal Doctrine argues that careful attention to the form and nature of doctrinal arguments can illuminate the structures by which the law operates. Such an understanding offers legal professionals and students the opportunity to better relate law to a specific case and to comprehend how legal argument, often conducted through doctrines, fits within the judicial system. Schlag and Griffin also show how the study of doctrine can illuminate the similarities between substantive legal fields, as we might see how the doctrine of "consent" in one field is similar to the concept of "assumption of risk" in another"--